Danhong Injection Protects Hemorrhagic Brain by Increasing Peroxiredoxin 1 in Aged Rats - Wang, Shang; Yu, Lie; Sun, Guifang; Liu, Yu; Hu, Wentao; Liu, Yanru; Peng, Tao; Wang, Xiaojun; Cheng, Jingliang; Sr, Aravintakumar; Qin, Bo; Lu, Hong (Frontiers in Pharmacology, 2020)
Intracerebral hemorrhage (ICH) is a severe cerebrovascular disease with high incidence, mortality and disability rate. Dan Hong Injection (DHI) is beneficial for ischemic stroke, but is prohibited for ICH due to risk of bleeding. The present study aimed to explore the potential therapeutic time window and molecular mechanism of DHI in the collagenase-induced ICH model in aged rats. DHI administration after ICH could significantly improve body weight and neurological deficits and reduce the hematoma volume and brain water content when compared to vehicle control. Furthermore, the protective effect of DHI administration on days 1 to 3 after ICH was superior to those on days 3 to 5 or 7 to 9 after ICH. DHI remarkably increased the Prx1 expression in astrocytes and reduced the expression of inflammatory factors TNF-α and IL-1β after ICH. However, the immediate treatment of Prx1 inhibiter Che after ICH abolished the protective effect of DHI. Che treatment reduced the expression of the Prx1 in astrocytes but increased the expression of TNF-α and IL-1β after ICH. DHI treatment could not reverse these changes. Therefore, the earlier Danhong Injection is administrated, the better the neuroprotective effect. DHI exerts antioxidative and anti-inflammatory function by increasing Prx1 in astrocytes. These present results may change the established understanding of DHI and reveal a novel treatment approach for ICH.